Identification of immune-related genes in thymus of breast cancer mouse model exposed to different calorie restriction - Ulu, Zehra Omeroglu; Ulu, Salih; Dogan, Soner; Tuna, Bilge Guvenc; Ozgenturk, Nehir Ozdemir (WALTER DE GRUYTER GMBH, 2019)
Introduction: In the present study, RNA sequencing-mediated transcriptome analysis was performed in order to elucidate the molecular mechanisms of the immune response for different types of calorie restriction (CR) application using MMTV-TGF-alpha. breast cancer mouse model. Methods: Animals were applied to three different dietary regiments; ad libitum (AL), chronic calorie restriction (CCR) and intermittent calorie restriction (ICR). Using thymus tissues, 6091 differentially expressed genes (DEGs) were identified in three dietary groups. After clustering of total of 6091 DEGs using Gene Ontology (GO) categories, a total of 400 genes were identified to be involved in immune system process (GO:0002376) GO categories. KEGG pathway and gene co-expression network analysis of these immune-related DEGs were done using String database. The results were confirmed with measuring mRNA expression levels of four selected immune-related DEGs genes (Casp3, Thy1, IL-16 and CD4) using quantitative real-time PCR (qPCR). Results: The expression levels of immune-related genes were different in three RNA-seq data. Conclusion: The results provide useful information to investigate the immune-related transcriptional profiling in thymus tissue of breast cancer mouse model applied to two different types of CR and to identify the specific functional immune related genes in response to CR during cancer development.
Keywords: Intermittent calorie restriction; Chronic calorie restriction; Thymus; RNA-seq; Immune-related genes; GROWTH-FACTOR-ALPHA; MAMMARY TUMORIGENESIS; DIETARY RESTRICTION; MICE; EXPRESSION; CYTOKINES; RECEPTOR; PROTEIN; Biochemistry & Molecular Biology